The Relationship Between Perceptions of Physical Activity, Attitudes, and Learning Motivation and the Learning Outcomes of Students at Al Madina Islamic Junior High School, Semarang - melati, azka; setyawati, heny (Journal of Physical Education and Sports, 2025)
This study aims to determine the relationship between perceptions of physical activity, attitudes, and learning motivation on student learning outcomes at Al Madina Islamic Junior High School, Semarang. The background of this study is based on the importance of physical activity, positive attitudes, and learning motivation as internal factors that influence student learning outcomes. The research method used is a quantitative descriptive approach with a correlational design. The population in this study were all students in grades VII and VIII of Al Madina Islamic Junior High School with a sample size of 221 students. Data collection was carried out using a questionnaire to measure perceptions of physical activity, attitudes, and learning motivation, while learning outcomes were obtained from report card grades. Data analysis used correlation techniques to determine the closeness of the relationship between variables. The results of the study indicate that there is a significant relationship between perceptions of physical activity, attitudes, and learning motivation partially and simultaneously on student learning outcomes. These findings are expected to be a reference for schools in improving learning programs, especially in the aspects of physical activity, the formation of positive attitudes, and increasing student learning motivation.